Influence of Generalized Discontinuous Pulse Width Modulation (GDPWM) on the DC-link Current and Voltage Ripple in Battery-fed PWM Inverter Systems - Mantzanas, Panagiotis; Bucher, Alexander; Kübrich, Daniel; Pawellek, Alexander; Hasenohr, Christian; Hofmann, Harald; Dürbaum, Thomas (2020 22nd European Conference on Power Electronics and Applications, EPE 2020 ECCE Europe, 2020)
In battery-fed pulse width modulated inverters, the DC-link capacitor represents a limiting factor in terms of power density. The size of the DC-link capacitor strongly depends on its current and voltage ripple. This paper investigates the modulation method 'Generalized Discontinuous Pulse Width Modulation' regarding DC-link current and voltage ripple in battery-fed pulse width modulated two-level three-phase voltage source-source inverters. 'Generalized Discontinuous Pulse Width Modulation' already proved to be effective in reducing the inverter switching losses. Parameter studies performed in this paper reveal that this modulation method also enables a reduction of the DC-link voltage ripple in comparison to the widely used modulation method 'centered space vector modulation'.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Adjustable speed drive; Passive component; Pulse Width Modulation (PWM); Simulation; Voltage Source Inverters (VSI)